2005
DOI: 10.1038/sj.leu.2403672
|View full text |Cite
|
Sign up to set email alerts
|

High IGFBP-3 levels in marrow plasma in early-stage MDS: effects on apoptosis and hemopoiesis

Abstract: The pathophysiology of the myelodysplastic syndromes (MDS) is incompletely understood. Tumor necrosis factor (TNF)alpha levels are elevated, particularly in early-stage MDS, and apoptosis in marrow cells is upregulated. Observations in other models have shown a role for insulin-like growth factor binding protein 3 (IGFBP-3) in TNFalpha-mediated apoptosis. We observed increased levels of IGFBP-3 in the marrow plasma of patients with MDS (P = 0.005) and hypothesized that altered IGFBP-3 levels contribute to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…function either as an antiapoptotic or proapoptotic factor depending on the cell type and condition (Granata et al, 2004). Wilson et al (2005) has reported that IGFBP3 may protect myeloid cells against apoptosis mediated by Fas ligand or tumor necrosis factor alpha (TNF␣). Accordingly, IGFBP3 could protect macrophage-like cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…function either as an antiapoptotic or proapoptotic factor depending on the cell type and condition (Granata et al, 2004). Wilson et al (2005) has reported that IGFBP3 may protect myeloid cells against apoptosis mediated by Fas ligand or tumor necrosis factor alpha (TNF␣). Accordingly, IGFBP3 could protect macrophage-like cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that IGFBPs are involved in the regulation of pro‐B cell development as well as regulation and proliferation of T cells [48, 49]. Furthermore, IGFBP‐3 has been suggested to promote proliferation of primitive HPC in vitro, whereas other authors did not observe an effect of IGFBP‐3 on GFU‐GM or BFU‐E [50, 51]. We have demonstrated that IGFBP‐1, IGFBP‐2, and IGFBP‐3 had no effect on proliferation or maintenance of a primitive immunophenotype in culture medium without cellular support.…”
Section: Discussionmentioning
confidence: 99%
“…Early stages of MDS display an increased apoptosis, contributing to ineffective hematopoiesis and peripheral cytopenia. Increased levels of tumor necrosis factor (TNF)a, 34 as well as the insulin-like growth factor-binding protein 3 (IGFBP-3), 35 has been observed and could be responsible for augmented TNFamediated apoptosis. Conversely, later stages of MDS present an excessive survival and leukemic evolution of MDS arises through lesions that inhibit apoptotic control mechanisms.…”
Section: Discussionmentioning
confidence: 99%